2005
DOI: 10.1016/j.limno.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Water quality in rural areas of the Czech Republic: Key study Slapanka River catchment

Abstract: The article evaluates the water quality in rural areas in the Czech part of Labe River catchment using the example of Slapanka River catchment. This river drains a typical landscape of Ceskomoravska Highland. Water quality in rural areas is still very low and the attention is paid to organic substances and nutrients. Increased amount of them in streams is caused mainly by agriculture and production of municipal wastewater resulting in increased eutrophication. A significant part of the article consists in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
5
7
0
Order By: Relevance
“…Concentrations of nitrate nitrogen in predominantly agricultural river catchments with a high β N,P index (the rivers Jevišovka, Sázava, Skalice, Oslava) have not changed over the long term. This is probably due to the constant or only slightly increasing trends in the application of mineral fertilizers to arable land in the period 1990-2008 (ME 2010), which is consistent with the results obtained by Judová and Janský (2005). In other river catchments, a slightly decreasing trend was found after 1990 ( Fig.…”
Section: Long-term Trends In Selected Water Quality Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…Concentrations of nitrate nitrogen in predominantly agricultural river catchments with a high β N,P index (the rivers Jevišovka, Sázava, Skalice, Oslava) have not changed over the long term. This is probably due to the constant or only slightly increasing trends in the application of mineral fertilizers to arable land in the period 1990-2008 (ME 2010), which is consistent with the results obtained by Judová and Janský (2005). In other river catchments, a slightly decreasing trend was found after 1990 ( Fig.…”
Section: Long-term Trends In Selected Water Quality Parameterssupporting
confidence: 89%
“…6(a)). Van Vliet and Zwolsman (2008) and Judová and Janský (2005) also reported the exponential growth of N-NO 3 -concentration dependent on flow as a consequence of surface runoff from arable land during heavy rains. Considering the short-term effect of floods and the range of the recorded values, this temporary increase does not appear to be problematic.…”
Section: Effects Of Flow On Selected Parameters Of Water Qualitymentioning
confidence: 91%
“…Therefore, our finding is in agreement with previous studies that agricultural land can be a primary cause of sediment, organic substances, and nutrient pollution (Berka et al. , 2001; Judová and Janský, 2005). Rice fields can be considered as the sink of sediment and organic nutrients.…”
Section: Discussionsupporting
confidence: 94%
“…The NPS pollution simulation results also show that organic nutrients are significantly correlated with sediment yield and comprise most of the nutrient load. Therefore, our finding is in agreement with previous studies that agricultural land can be a primary cause of sediment, organic substances, and nutrient pollution (Berka et al, 2001;Judová and Janský , 2005). Rice fields can be considered as the sink of sediment and organic nutrients.…”
Section: Nps Pollution Under Different Lulcssupporting
confidence: 94%
“…The runoff from cultivated farmlands and wastewater from residences without adequate sanitation were identified as the main pollution sources. Contamination originating from agriculture is also a problem in this area [43]. Ntislidou et al (2012) in a case study from river basin Kosynthos, in Greece conducted in June 2011, reported levels of phosphates ranging from 0.022 to 0.146 mg/L, respectively.…”
Section: Phosphorus Compoundsmentioning
confidence: 99%